Role of gut microbiota in thalassemia: a review of therapeutic prospects - Guanjun Chen; Yulan Li; Shirui Wei; Xinyu Wang; Zheshu Kuang; Weiming Guo; Jianbin Qin; Tianjun Huang; Youlin Li; Chunjiang Zhu (Frontiers in Physiology)
In recent years, the study of gut microbiota has gradually become a research hotspot in the field of medicine, as gut microbiota dysbiosis is closely related to various diseases. Thalassemia, as a hereditary hemoglobinopathy, has a complex pathophysiological mechanism, and traditional treatment methods show limited efficacy. With a deeper understanding of the gut microbiome, researchers have begun to focus on its role in the pathogenesis of thalassemia and its therapeutic effects. This article aims to review the role of gut microbiota in thalassemia and its potential therapeutic prospects, analyze the latest research findings, and explore the impact and mechanisms of gut microbiota on patients with thalassemia, with the goal of providing new ideas and directions for future research and clinical treatment of thalassemia.